2014
DOI: 10.1371/journal.pone.0107339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Negative Pressure Wound Therapy on Mesenchymal Stem Cells Proliferation and Osteogenic Differentiation in a Fibrin Matrix

Abstract: Vacuum-assisted closure (VAC) negative pressure wound therapy (NPWT) has been proven to be an effective therapeutic method for the treatment of recalcitrant wounds. However, its role in bone healing remains to be unclear. Here, we investigated the effects of NPWT on rat periosteum-derived mesenchymal stem cells (P-MSCs) proliferation and osteoblastic differentiation in a 3D fibrin matrix. P-MSCs underwent primary culture for three passages before being used to construct cell clots. The fibrin clots were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
7
21
0
Order By: Relevance
“…In addition, negative pressure induced expression of HIF1α that is responsible for upregulation of a broad range of angiogenic factors, including VEGF, SDF1, and PDGF (Rey & Semenza, ). These findings are consistent with Yang et al, who reported increased ALP activity and synthesis of type I collagen and VEGF by human MSCs with 30‐min treatments of negative pressure applied twice daily (Yang et al, ), and those of Zhu et al who reported increased ALP activity and expression of COL1A1, osteocalcin, and ALP by rat MSCs after 3 and 7 days of continuous negative pressure (Zhu et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, negative pressure induced expression of HIF1α that is responsible for upregulation of a broad range of angiogenic factors, including VEGF, SDF1, and PDGF (Rey & Semenza, ). These findings are consistent with Yang et al, who reported increased ALP activity and synthesis of type I collagen and VEGF by human MSCs with 30‐min treatments of negative pressure applied twice daily (Yang et al, ), and those of Zhu et al who reported increased ALP activity and expression of COL1A1, osteocalcin, and ALP by rat MSCs after 3 and 7 days of continuous negative pressure (Zhu et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with findings of Zhu et al with rat periosteum‐derived MSCs in a 3D fibrin matrix. Specifically, they observed that cells were more spread in their fibrin gels and exhibited increased cell density and ALP activity with 72 hr of continuous negative pressure (−125 mmHg; Zhu, Yu, Qi, Li, & Hu, ). Switching to human and rat MSCs, it was found that MSCs cultured on BRM exhibited increased expression of osteoblastic genes ALP, OPN , and COL1A2 under negative pressure.…”
Section: Discussionmentioning
confidence: 99%
“…An evident example was the wide variation in wound area and time of wound closure. These considerations are important because they are directly associated with the tensile force experienced by the tissue, which profoundly affect the speed and quality of skin repair [59, 60]. Our findings show that 20% of the studies that utilized fractions neglected the analysis of wound closure, an essential piece of information to assess the ability of any intervention to stimulate the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…During the formation of granulation tissue, there is predominance of sulfated molecules which attract water, facilitating the cellular migration, and also serve as a support structure for the first formed collagen (type III collagen) [65]. There are enough evidences that the synthesis and differentiation of cells and matrix components are crucial for a normal wound closure [60]. It is already known that the oxidative stress induces cell damage, lipid, protein, and nucleic acids oxidation [66, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Also, with its ability to promote healing of fractures as shown by Zhu et al by stimulating mesenchymal stem cell proliferation and osteogenic differentiation NPWT may play and stimulate healing of fractures itself. 6 This study is a prospective randomised control study of 30 patients which aims to study the utility of NPWT in compound tibial fractures with respect to its impact on wound healing and soft tissue cover in a setting of a tertiary care centre. The observations of this study were subjected to comparison with the observations made by different authors.…”
Section: Discussionmentioning
confidence: 99%